The Supplement of Reading Figures of Understanding in Romantic Theory and Practice - Rajan, Tilottama (Cornell University Press, 2018)
Tilottama Rajan illuminates a crisis of representation within romanticism, evident in the proliferation of stylistically and structurally unsettled literary texts that resist interpretation in terms of a unified meaning. The Supplement of Reading investigates the role of the reader both in romantic literary texts and in the hermeneutic theory that has responded to and generated such texts. Rajan considers how selected works by Coleridge, Wordsworth, Blake, Shelley, Godwin, and Wollstonecraft explore the problem of understanding in relation to interpretive difference, including the differences produced by gender, class, and history.